Javno mnenje o varnostnih temah - Malešič, Marjan (Teorija in praksa, 2007)
Some key questions on rationality (responsiveness), consistency and reliability of public opinion have been raised in scientific literature and in professional and lay public in recent years. The authors reply to these questions on the basis of public opinion results obtained in surveys carried out in Slovenia after 1990, examining the following group of variables: perception of threats, membership of Slovenia in NATO, the role of armed forces in contemporary society and their functions, and trust into Slovenian Army, the way of its manning and operating costs. The authors found out that Slovenian public supported crucial projects of the state in security field; however it did not always follow the opinion of political elite. Nor did the public follow its own general value orientation while supporting those projects. The data reveal that public opinion about security issues has been relatively stable after 1990 whereas greater changes have been most often related to the changed circumstances and fresh information.
Keywords: Javno mnenje; Public opinion; Nacionalna varnost; National security; International security; Mednarodna varnost; Slovenian Armed Forces; Slovenian Army; Slovenska vojska; Armed forces; Oborožene sile; Družba; Society; Slovenija; Slovenia; NATO